Combining personalised medicine and patient-centered care in breast cancer: a systematic review. (20th October 2021) - Castagna, C; Pellegrino, R; Morsella, A; Boccia, S; Pastorino, R; De Belvis, AG
Abstract: Background: Breast Cancer (BC) is estimated to cause 2.3 million yearly new cases worldwide. Efforts towards standardized, quality assured and effective care have led to an increasing complexity and specialization of BC management. This systematic review's aim is to describe the state-of-the art of available literature investigating the enactment of personalised medicine and patient-centered care models in BC practice and build a framework towards personalised BC care within a patient-centered model. Methods: Databases were searched to retrieve articles reporting on BC management, evaluated in terms of patient-centered and personalised medicine approaches, assessing success factors or limits, in English, from the inception to December 2020. The investigated dimensions for patient-centered care models were audits, communication, informative systems and multidisciplinarity. Concerning Personalised Medicine, investigations were related to molecular boards, genetic testing and shared-clinical decision-making. Results: Out of 1885 records, 25 studies were included in the qualitative analysis. The main success factors are multi-professional collaborations with defined roles and responsibilities, training programs on genomic tools and adequate communication strategy (i.e universal genomic language) to involve patients in the decision-making process. Among detected barriers, delays in genetic testing use were linked to the lack of public reimbursement and of clarity in timing and appropriateness. Conclusions: Both these models are complementary and needed to ensure effective changes in the path of BC patient management. Our framework aims to the transformation of standardized application of evidence-based medicine into a dynamic and personalised care pathway. Key messages: The combination of the two care delivery approaches is scarcely investigated in literature. Our framework would allow to fill such gap and attributes a key role to sharing the decision-making process.